Kesalahan Berbahasa pada Anak Umur 4 Tahun Akibat Kasus Congenital Deafness atau Hearing Loss - Ayu Kameliya; Meilan Arsanti (MISTER: Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
Congenital deafness is a condition of hearing loss that occurs from birth and can be caused by genetic or non-genetic factors. This condition can affect a child's communication abilities and language development. The prevalence of congenital deafness is estimated to occur in 1-3 out of 1000 births. Currently, there are various technologies and therapies being developed to treat congenital hearing loss, such as numerical gesture detection applications and auditory nerve implants. Early diagnosis and appropriate intervention can help children overcome difficulties in language and communication. This research was written based on what was researched and studied through this case. It can be concluded that this congenital disorder is very fatal because if it is left in childhood, it will cause prolonged deafness and there is no other cure other than prolonged therapy.